(untitled) (TAMADDUN NURI JURNALI, 2024)
This article deals with speech etiquette and their use in today’s society place, speech etiquette has a special place in linguistics as an important factor regulating cultural relations between members of society, a comparative analysis of speech etiquette rules is revealed. The results of this scientific research speak about language and intercultural relations through the study of speech etiquette.